2005
DOI: 10.2170/jjphysiol.s642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Norepinephrine and Histamine on Vascular Resistance in Isolated Perfused Mouse Liver

Abstract: Mice have frequently been used for a variety of physiological studies because of the development of genetic engineering. However, the characteristics of hepatic vessels such as the vascular resistance distribution and the reactivity to various vasoconstrictors are not known in mice. We therefore determined the basal levels of segmental vascular resistances and the effects of histamine and norepinephrine on the vascular resistance distribution of mice. The liver of male non-inbred ddY mice was excised and perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…During mouse systemic anaphylaxis, PAF could be released from sensitized mast cells and macrophages (11). In addition, another anaphylactic mediator of histamine also induced liver weight loss in isolated mouse livers perfused at constant flow (24). This liver weight loss, an indicator of reduced hepatic blood volume caused by the anaphylactic mediator, suggests that this chemical mediator also acts to reduce the intrahepatic blood volume in anesthetized mice exposed to systemic anaphylaxis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…During mouse systemic anaphylaxis, PAF could be released from sensitized mast cells and macrophages (11). In addition, another anaphylactic mediator of histamine also induced liver weight loss in isolated mouse livers perfused at constant flow (24). This liver weight loss, an indicator of reduced hepatic blood volume caused by the anaphylactic mediator, suggests that this chemical mediator also acts to reduce the intrahepatic blood volume in anesthetized mice exposed to systemic anaphylaxis.…”
Section: Discussionmentioning
confidence: 98%
“…The basic method for isolated liver perfusion was described previously (24,25). The liver was perfused at a constant flow rate in a recirculating manner via the portal vein with the diluted blood.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that PAF [8] and histamine [9] could constrict the hepatic vasculature in isolated perfused mouse livers. We for the first time reported that in anesthetized mice, PAF and histamine increased Ppv, which reached the maximal levels of 10-11 cm H 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…ac.jp. the isolated perfused mouse liver preparation in which the sinusoidal pressure can be measured with the double occlusion method [5].…”
Section: Introductionmentioning
confidence: 99%